Dinamika Media Massa Dalam Era Digital: Analisis Terhadap Evolusi Praktik Jurnalistik Kontemporer - Tika Mutia; Ajani Restianty; Sultan, Moehammad Iqbal; Andi Subhan Amir (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
This article examines the evolution of contemporary journalistic practices in the context of the mass media transformation in the digital era. Employing a qualitative approach, through document analysis and in-depth interviews with media practitioners, the study reveals how digitalization affects news processes and journalistic dynamics. Focusing on the period from 2015 to 2023, the research finds that the digital revolution has brought about significant changes in news production, distribution, and consumption. Notably, there has been an increased integration of digital technology in news gathering and presentation, as well as a shift in media-audience interaction. The article also highlights the challenges faced by journalists in adapting to new technologies and changing audience preferences, including issues of speed versus accuracy and the struggle against the spread of misinformation. The findings contribute to a deeper understanding of how contemporary journalistic practices adapt and evolve in an increasingly digital society, as well as its implications for the future of the news industry.